Change and continuity in spatial planning :metropolitan planning in Cape Town under political transition - Watson, Vanessa (My University, 2002)
South Africa in 1994 was a place of great promise, for many. A relatively peaceful transformation from authoritarian rule, based on the ideology of apartheid, to a liberal democracy had been achieved, and the ruling majority party, the African National Congress (ANC), espoused a policy of equality and democracy. For those spatial planners both within and outside government structures who had supported these ideals, it appeared as if planning could at last shake off the shackles of apartheid and begin to play an important role in building a new and better society. New ideas about spatial planning (not too different from what is now known as "new urbanism" and the "compact city") were gaining increasing acceptance in professional planning circles, coinciding with a demand that the towns and cities divided by racial and spatial segregation now be restructured, reintegrated and made accessible to the poor (RDP 1994). If ever the time was ripe for spatial planners to demonstrate that their traditional humanitarian and environmental concerns could find concrete expression in the shaping of the built environment to these new ends, it was during South Africa's political transition. (Abbreviation Intro)
Submitted as the requirement of TRPL901 -PhD Thesis Doctor of Philosophy (Town and Regional Planning) Faculty of the Built Environment University of the Witwatersrand, Johannesburg
Keywords: City planning--South Africa--Cape Town; Urban policy--South Africa--Cape Town; Municipal government--South Africa--Cape Town; South Africa--Politics and government--1994-; Metropolitan areas--South Africa--Cape Town--Planning